Annie's promise - Levitin, Sonia, 1934- (New York : Aladdin Paperbacks, 1996)
Her experiences at a summer camp in the California mountains in 1945 gives twelve-year-old Annie Platt new insight into her overprotective family of German-Jewish immigrants.
Sequel to: Silver days.
6.5
5-8
5-8
Wilson's Junior High School
School Library Journal starred
Keywords: World War, 1939-1945 -- United States -- Juvenile fiction; Camps -- Fiction; World War, 1939-1945 -- United States -- Fiction; Family life -- Fiction; Jews -- Fiction; German Americans -- Fiction; Camps -- Fiction; World War, 1939-1945 -- United States -- Fiction; Family life -- Fiction; Jews -- United States -- Fiction; German Americans -- Fiction